2007
DOI: 10.1093/ps/86.3.517
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Different Dose Response in Turkeys When Fed 2-Hydroxy-4(Methylthio) Butanoic Acid Versus dl-Methionine

Abstract: In broilers, 2-hydroxy-4(methylthio) butanoic acid (HMTBA) can elicit a different dose response relative to dl-Met (DLM) such that birds could have lower gain responses at deficient TSAA concentrations but greater gain responses at maximum response concentrations. Two experiments tested if the 2 Met sources have a different dose response in 1-d-old turkeys using a 2 x 4 factorial plus a control design with 8 replicates of 12 toms per treatment. 2-Hydroxy-4(methylthio) butanoic acid and DLM were supplemented at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…With this evaluation, the digestible Met+Cys was same in the diets independent of sources evaluated, reducing the chances of equivocal equivalences, and bioavailability in consequence, or effects without efficient measurement of sources. Thus, the evaluations and applications with methionine sources should be performed by equimolar basis, allowing better results in alternative source efficiency and poultry performance, corroborating with (Gonzales‐Esquerra et al., ; Vazquez‐Anon, Kratzer et al., Vazquez‐Anon, Gonzalez‐Esquerra et al., ).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…With this evaluation, the digestible Met+Cys was same in the diets independent of sources evaluated, reducing the chances of equivocal equivalences, and bioavailability in consequence, or effects without efficient measurement of sources. Thus, the evaluations and applications with methionine sources should be performed by equimolar basis, allowing better results in alternative source efficiency and poultry performance, corroborating with (Gonzales‐Esquerra et al., ; Vazquez‐Anon, Kratzer et al., Vazquez‐Anon, Gonzalez‐Esquerra et al., ).…”
Section: Resultssupporting
confidence: 70%
“…The efficacy clearly depends upon the type of diet and supplementation level, with supplemental, amino acid‐based, purified experimental diets apparently favouring DLM‐99%. However, poultry fed commercial diets containing HMTBA may have better responses than poultry fed diets with DLM‐99% at practical levels of supplementation (Gonzales‐Esquerra et al., ;Vazquez‐Anon, Kratzer, Gonzalez‐Esquerra, Yi, & Knight,; Vazquez‐Anon, Gonzalez‐ Esquerra et al.,). This efficacy is such that HMTBA is used as a methionine source in the poultry industry in United States of America, with an 85 to 88% bioefficacy level for liquid methionine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DL-methionine (DLM) or DL-methionine hydroxy analogue (MHA) [43]. Chemically, MHA is not an amino acid but a metabolic precursor of DLM and a very effective source of supplemental Met [7, 41]. Some studies have revealed MHA to be more effective in improving the antioxidant status of chickens and turkeys than DLM [25, 38, 42].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that these two methionine sources had a different dose-response, with HMTBA outperforming DL-Met at commercial levels and DL-Met outperforming HMTBA at total dietary sulfurcontaining amino acid (TSAA) deficient levels (41). Similar results were observed in turkeys, with feeding supplemental HMTBA to young male turkeys for 21 days leading to a lower growth but greater maximum response compared with DL-Met at TSAA deficient levels (42).…”
Section: The Bio-efficacy Of L-met Dl-met and Hmtba In Poultrymentioning
confidence: 87%